Pengaruh Faktor-Faktor Kualitas Jasa terhadap Kepuasan Nasabah (Study Kasus di Bank Syariah Mandiri Cabang Surakarta) - Anggit Utami; Y Anni Aryani (Jurnal Akuntansi dan Bisnis, 2004)
Quality and customer satisfaction are two keywords for organization survival,especially in a high competition era. The research uses 53 samples, they are Syariah Mandiri Bank branch Surakarta customer. The variables being examined are tangibles, responsiveness, assurance, empathy, reliability, and customer satisfaction.The result of regression analysis shows that just assurance and responsiveness variables had influence on customer satisfaction, while other independent variablesare not relevant with the hypothesis.